Rapid amplification of genetically modified organisms using a circular ferrofluid-driven PCR microchip - Sun, Yi (2012)
The use of genetically modified organisms (GMOs) as food and in food products is becoming more and more widespread. Polymerase chain reaction (PCR) technology is extensively used for the detection of GMOs in food products in order to verify compliance with labeling requirements. In this paper, we present a novel close-loop ferrofluid-driven PCR microchip for rapid amplification of GMOs. The microchip was fabricated in polymethyl methacrylate by CO2 laser ablation and was integrated with three temperature zones. PCR solution was contained in a circular closed microchannel and was driven by magnetic force generated by an external magnet through a small oil-based ferrofluid plug. Successful amplification of genetically modified soya and maize were achieved in less than 13 min. This PCR microchip combines advantages of cycling flexibility and quick temperature transitions associated with two existing microchip PCR techniques, and it provides a cost saving and less time-consuming way to conduct preliminary screening of GMOs.